2011 19th International Conference on Geoinformatics 2011
DOI: 10.1109/geoinformatics.2011.5981176
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of rainstorm waterlogging on subway in central urban area of Shanghai, China based on scenario simulation

Abstract: Most of cities in the world like Shanghai have a large number of underground facilities including public transport and commercial facilities such as shopping malls, subway, parks, etc. The safety of underground spaces has become a very important aspect of urban safety. Underground facilities are very much vulnerable to waterlogging disasters. Urban waterlogging disasters have been causing havoc to public transport, residences and underground facilities (subway, commercial facilities). Due to the influence of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…We found that the percent coverage of building made a larger contribution to urban waterlogging risk spots than the pavement did, which was consistent with Quan et al's [69] study. However, Wang et al [14] found the pavement contributed more than the building did.…”
Section: Fractionsupporting
confidence: 82%
“…We found that the percent coverage of building made a larger contribution to urban waterlogging risk spots than the pavement did, which was consistent with Quan et al's [69] study. However, Wang et al [14] found the pavement contributed more than the building did.…”
Section: Fractionsupporting
confidence: 82%
“…Researchers delved into weather-related disruptions and disasters in subway traffic, such as fire (Rie and Ryu, 2020; Giachetti et al , 2017), earthquakes (Fan et al , 2021), hurricanes (Zhu, Yuan, et al , 2016; Zhu, Yuan, et al , 2017) and weather conditions (Chan and Schofer, 2016; Diab and Shalaby, 2020; Wang et al , 2020). Quan et al (2011) used scenario simulation to focus on the impact of rainstorms with different return periods on the Shanghai Metro. Lyu (2018) conducted a flood risk assessment of Guangzhou's subway system, considering 12 factors such as rainfall, altitude, slope and subway line density.…”
Section: Strategies Of Enhancing Resilience Under Various Scenariosmentioning
confidence: 99%
“…Connection linking flood events on the surface with vulnerability to flooding of underground subway infrastructure. (Lyu et al 2016) b. Frameworks based on decision-making methods as networks theory and analytic hierarchy process for assessing the flood evolution process and consequences in underground spaces (Lyu et al 2018;Wu et al 2018a) c. Integration of a stormwater management model into a geographical information system to evaluate the flood risk in a specific metro system (Herath and Dutta 2004;Li et al 2018a;Lyu et al 2019a) d. Methodologies to obtaining risk level studying both flood intensity and evacuation difficulty in underground spaces like metro stations (Han et al 2019) e. Analysis of metro systems resilience in the face of flood hazards, studying the components failure steps (Gonzva et al 2017) f. Risk assessment for metro systems flooding events based on regional flood risk evaluation methods (Lyu et al 2019b) g. Evaluation of the waterlogging risk of metro infrastructure caused by rainstorm in a specific Metro system (Quan et al 2011) h. Assessment of the risk in a specific metro system against fluvial flooding (Compton et al 2009) i. Evacuation of ridership from inundated underground space (Ishigaki et al 2008(Ishigaki et al , 2010 Table 3.…”
Section: Study Approach Reviewed Sourcesmentioning
confidence: 99%